TEORI MASLAHAH DALAM EKONOMI ISLAM : (FIKIH MUAMALAH) - Zaenol Hasan (Sekolah Tinggi Ilmu Syariah Nurul Qarnain Jember, 2022)
: Economics is an inseparable part of human life, with economic activity, humans can fulfill their needs such as eating, drinking, living, and carrying out other activities. An economy that cannot be fulfilled, of course, will have a significant impact on human life. For this reason, the economy is only part of the human life sector and must be carried out based on the laws that Allah has given. In this case, Islam has principles that are intended for humans, so that in economic activity can be lucky, useful, and share the grace of the universe (Maslahah 'ammah). There are three points of discussion (a) How is Maslahah Mursalah in the view of the Ulama? (b) What are the divisions of Maslahah in Islam? (c) How are the theories of Maslahah in Islamic Economics? The type of research in this writing is qualitative with library research. Library research is defined as a study or research on library sources and using written materials in the form of books related to the focus of this research. This research is descriptive analysis, which is a method that describes and explains systematically. The results of the discussion in this study are as follows, In principle, maslahah is taking benefits and rejecting misfortune in order to maintain the goals of shara', Maslahah dlaruriyyat is something that must be realized in order to realize the benefits of religion and the world. There are five things included in it, namely: Keeping religion (حفظ الدين), Keeping the soul (حفظ النفس), Keeping offspring (حفظ النسل), Keeping property (حفظ المال), Keeping reason (حفظ العقل). All forms of muamalah must fulfill the following principles: وجود التبادل (the existence of exchange). وجود التعادل (the existence of justice or equality), وجود التراضى (the voluntariness of both parties), عدم الغرار (no speculative), عدم الربا (does not contain usury) and عدم الضرر (no harm).